PENGARUH KUALITAS PRODUK DAN PROMOSI PADA MARKETPLACE SHOPEE TERHADAP KEPUTUSAN PEMBELIAN DI SHOPEE (STUDI KASUS PADA KARYAWAN BNI DIVISI CONTACT CENTER SUDIRMAN JAKARTA - Meilinda Torihoran; Cundo Harimurti (JAMBIS : Jurnal Administrasi Bisnis, 2022)
The purpose of this study was to determine the effect of Product Quality and Promotion on Purchase Decisions. The theory used in this study refers to the opinion of Kotler (2009: 188) which states that purchase decisions are consumers'willingness to buy a product or not. This research was conducted using quantitative methods through the distribution of questionnaires. The sample consisted of 56 respondents who were selected from a population of 56 individuals using the saturated sampling method. The results of data analysis using partial and multiple linear regression analysis with the help of SPSS version 25 show that partially product quality has a positive and significant effect on purchasing decisions with a value of 63.5%, and promotions also has a positive and significant effect on purchasing decisions with a value of 36.5%. The F test proves that the Product Quality and Promotion variables simultaneously have a positive and significant effect on Purchase Decisions with an fcount value of 48.75, greater than ftable (3.17). In addition, the positive and significant influence can also be seen from the value of the determinant coefficient, i.e. 64.8%, with the remaining 35.2% influenced by other variables not examined in this study